Pengaruh Promosi Terhadap Keputusan Berkunjung Wisatawan ke Objek Wisata Pemandian Pincuran 7 Kabupaten Sijunjung - Endang Irhartini; Kasmita Kasmita (Departemen Pariwisata Universitas Negeri Padang, 2023)
This study aims to obtain results on how influential promotion is on tourists' visiting decisions at the Pincuran 7 Bathing tourist attraction in Sijunjung Regency. The type of research used is quantitative with a causal associative approach. The research sample is visitors who have visited the Pincuran 7 Baths tourist attraction using the Purposive Sampling technique. Data were collected by distributing closed questionnaires that had been prepared and had passed the validity and reliability trials, and used a Likert scale with linear regression analysis and were then given to respondents. very good category, (2) The decision to visit to get the proportion (59.60%) is in the sufficient category, (3) The results of simple linear regression hypothesis testing obtained F count 5.347 with a significance of 0.023> 0.05. get poetry that the promotion variable can explains the decision to visit significantly, then the R square is 0.052 so that it can be interpreted that the effect of promotion on the decision to visit is as much as 5.2%.